Pakistan Rural Household Panel Survey (PRHPS), 2012 - International Food Policy Research Institute; Innovative Development Strategies (International Food Policy Research Institute, 2014)
Pakistan Rural Household Panel Survey (PRHPS), 2012 is the 1st round of the Rural Household Panel Survey, which aims to provide a quantitative basis to identify and address urgent economic policy priorities. The RHPS covers 2090 households in 76 primary sampling units in the rural areas of three provinces namely: (i) Punjab; (ii) Sindh; and (iii) Khyber Pakhtunkhwa (KPK). The sample is nationally representative of the rural areas of the three provinces. This survey collected information on a large number of topics, such as sources of income, nature of employment, consumption patterns, time use, assets and savings, loans and credit, education, migration, economic shocks, participation in social safety nets, and household aspirations. Six survey instruments were developed to collect this information. These included three household-level questionnaires (two were designed to collect household information on various household and individual level aspect by males and females separately, and the third was an aspirations questionnaire, conducted on a household member between ages 18-35), a community questionnaire, a price questionnaire, and a school questionnaire.